Hypnosis and its applications in Dentistry (Research, Society and Development, 2024)
Objective: Research through a literature review the use of hypnosis as an anxiety control technique in dentistry. Methodology: Searches were conducted using descriptors in PubMed Central, BVS/BIREME, Web of Science, SciELO, The Cochrane Library, and Google Scholar. In addition, considering that this article is a literature review, the view of Mattos (2015) was used to structure this work. Results: Our research resulted in 20 articles. The Federal Council of Dentistry (CFO) Decision 45/2008 was used as a reference for complementary standards for qualification in integrative and complementary oral health practices. Conclusion: Despite the mysticism that surrounds it, hypnosis is, in fact, a scientifically proven tool that helps to reduce costs, as it can be an alternative to anesthetics and medications with analgesic effects. This makes it possible to treat patients' adversities and promote comfort. Scientific studies in this area have great potential in dental clinics and other oral hygiene environments.